L-(+)-Tryptophan methyl ester derived polymeric microbeads as an efffiicient heterogeneous catalyst for green synthesis of 2-amino-4-(nitromethyl)-4H-chromene-3-carbonitriles - Poslu, Ayse Halic; Osman, Bilgen; Kaya, Yunus; Koz, Omer; Koz, Gamze (Tubitak Scientific & Technological Research Council Turkey, 2022)
The cross-linked microbeads with average diameter of 106-300 mu m, [poly(EGDMA-MATrp)], were obtained by copolymerization reaction of N-methacryloyl-L-(+)-tryptophan methyl ester (MATrp) with ethylene glycol dimethacrylate (EGDMA) and successfully applied as a heterogeneous catalyst in conjugate addition reaction of nitromethane to substituted 2-iminochromenes in aqueous media. A variety of 2-amino-4-(nitromethyl)-4H-chromene-3-carbonitriles has been synthesized in good yields. Polymeric microbeads were very durable and reused 5 times without a significant loss of activity. DFT calculations and experimental results revealed the significant role of Tr-Tr interactions as well as hydrogen bonding in the reaction mechanism.
Keywords: Polymeric microbeads; L-(+)-tryptophan methyl ester; nitromethane addition; Tr-Tr interaction; DFT calculation